IS THE HIGH FREQUENCY OF DIABETES TYPE 2 IN CHRONIC HEPATITIS C VIRUS INFECTION DUE TO STRONG FAMILY HISTORY? - Qureshi, Fawad; Qureshi, Faisal; Fasih, Qudsia Anjum; Zuberi, Sarwar (Journal of Ayub Medical College Abbottabad, 2005)
Various epidemiological studies have suggested that hepatitis C virus (HCV) infection is a risk factor for the development of diabetes mellitus (DM) type 2.1-6 The etiological factors were initially thought to be cirrhosis but further studies differentiating between HCV and hepatitis B virus (HBV) related infection have shown that patient with HCV infection have a higher prevalence of Diabetes mellitus type-2.7 A retrospective analysis of 1117 patients with chronic viral hepatitis found that diabetes was present in significantly more patients with hepatitis C compared to hepatitis B virus (HBV) infection (21 versus 12 percent).2 HCV genotype 2a was over represented among the diabetic patients. In another case control trial, the prevalence of HCV infection was significantly higher among patients with diabe-tes mellitus compared to controls (4.2 versus 1.6 percent). Patients undergoing liver transplantation for HCV also appear to be at increased risk for developing diabetes mellitus following transplantation 8. The cause of these associations is unknown, but their magnitude may be overestimated based upon the retrospective nature of the reports and due to some of the following factors.9 a. Patients with diabetes have more parenteral exposures than the general population, placing them at increased risk for transmission of viruses. b. HCV infection becomes chronic more often than HBV infection. c. Not all studies are controlled for the presence of cirrhosis, which may be associated with impaired glucose tolerance. Only one study that we came across which was from Saudi Arabia had mentioned other variables and showed that Anti-HCV-positive type-2 diabetics, when compared to non-diabetics, had a higher Body mass index (BMI), a frequent family history of DM, elevated serum transaminases, thrombocytopenia, and liver cirrhosis on biopsy.10 With this hypothesis in mind, we conducted the present study to determine other variables such as familial inheritance as the cause of higher frequency of DM type 2 among patients with HCV infection.